LES SÉRIES CHRONOLOGIQUES Á MÉMOIRE LONGUE : PROBLÈME D’ESTIMATION ET APPLICATION AUX DONNÉES RÉELLES - Imane EL WAHLI (Faculté des Sciences de Rabat, 2021)
Several empirical researches on financial market data have revealed many properties of time series, mainly the behavior of long memory, in the sense of hyperbolic decay of autocorrelation. This thesis then focused on the estimation and modelling of persistence in time series and understanding its dynamics.
LONG MEMORY TIME SERIES: ESTIMATION PROBLEM AND APPLICATION TO REAL DATA
Keywords: Mathématiques Appliquées; Mathématiques Appliquées